Females are mosaics : X inactivation and sex differences in disease - Migeon, Barbara R. (Oxford University Press, 2014)
Women can be described as genetic mosaics because they have two distinctly different types of cells throughout their bodies. Unlike males, who have one X chromosome, females have two X chromosomes in every cell. Much has been written about the Y chromosome and its role in inducing maleness. This is the only book about the X chromosome as a key to female development and the role of X-related factors in the etiology of sex differences in human disease. This new edition reflects research advances from the six years since the widely praised first edition. New advances include knowledge of species differences in mammalian X inactivation processes and silencing of the inactive X chromosome.